Decision Support System On Computer Maintenance Management SystemUsing Association Rule and Fisher Exact Test One Side P-Value - Farid Sukmana; Fahrur Rozi (Universitas Ahmad Dahlan, 2017)
Decision-makinghas been growth rapidly and many methods can used. Thus, how to apply that methode not only fast but also right. One of implementationdecision making is decision support system in Computer Maintenance Management System (CMMS). This research using data test with Association Rule and Fisher Exact One Side P-Value from same problems in Computer Maintenance Management System (CMMS). Object from this research to get pattern of association between symptom and root cause, to prove relation those variable. Previous research prove any relation between that two variable when use Association Rule and Pearson Chi-Square but many rule must eliminated because not ineligable from Pearson Chi-Square. The meaning of this research to confirm proof of test relation between symptom and root cause in CMMS. And hope with this result of test can make strength hypothesis from previous research.